Optimization and Analysis of Double-circular-arc Harmonic Gear based on Genetic Algorithm - Zhonglong Luo; Xiaochuan Peng (Jixie chuandong)
The "dual-conjugated" phenomenon is generated in the process of the double-circular-arc harmonic transmission， which has an important influence on the carrying capacity of harmonic gear transmission. Therefore， an optimization method based on genetic algorithm to optimize the "dual-conjugated" interval is proposed. Firstly， based on the theoretical conjugate tooth profile of the flexspline obtained by the envelope method， then， one parameter optimization model （based on genetic algorithm） of double-circular-arc harmonic gear is established， which taking the fit degree of the two conjugate tooth profiles as the optimized goal. By using this model， the parameters of the flexspline are optimized quickly. The results show that this optimization method can optimize more parameters contemporary and reduce the calculation time. Through analyze the single parameter sensitivity of the optimized parameters， it is found that the objective function has a low sensitivity to the arc radius of convex and concave tooth， and the tooth thickness ratio. Therefore， to control the manufacturing accuracy of the flexspline and increase the "dual conjugate" interval， one of the useful way is that relax the size error of low sensitivity parameters and control the size error of high sensitivity parameters appropriately.